Respuesta :

Answer:

Option D.

Step-by-step explanation:

The given expression is

[tex]x^6+x-66[/tex]

It is a polynomial.

(x-c) is a linear factor of polynomial p(x) if p(c)=0.

Substitute x=-1 in the given expression.

[tex](1)^6+(1)-66=-64\neq 0[/tex]

It means (x+1) is not a linear factor of given expression.

Substitute x=-2 in the given expression.

[tex](-2)^6+(-2)-66=-4\neq 0[/tex]

It means (x+2) is not a linear factor of given expression.

Substitute x=-4 in the given expression.

[tex](-4)^6+(-4)-66=4026\neq 0[/tex]

It means (x+4) is not a linear factor of given expression.

None of the given options are a linear factor of given expression.

Therefore, the correct option is D.

Answer:

none of the above

Step-by-step explanation: